Monetary policy reaction functions and saving-investment correlations: Some cross-country evidence - Erkki Koskela; Matti Virén (Bank of Finland, 1990)
Keeping the finding of Feldstein and Horioka (1980) - that countries investment rates are highly correlated with their national saving rates - as a starting point this paper examines the possibility that . monetary policy reactions to target the current account mi.ght explain saving-investment correlations. The OLS, robust and variable-parameter estimates of the linear reaction functions with quarterly data from Germany, Italy, Japan and the United States suggest - the United States being an exception - that the current account deficit leads to tighter money, ceteris paribus. The threshold estimation results indicate, howeyer, that the reaction functions are non-linear in terms of the current account variable; monetary policy reacts stronger to deficits than to surpluses. Moreover, allowing for asymmetricity makes the performance of the reaction functions better and parameter estimates more preci se. We are tempted to i nterpret ·fi-ndi ngs as gi vi ng considerable support for the notion that current account has been a significant target for monetary policy in Germany, Italy and Japan. This in turn might explain the high saving-investment correlations even in the presence of highly mobile international capital movements.
URN:NBN:fi:bof-201807311796
Keywords: 330